(3TQM GdebOeI GdLRhdjI aj GdfMh ddLRhdis - (3CHhYdj YeQ Hf eMeOGdTdhHjf GdCROis; (3GHf jddHNJ , YjSi Hf YHO GdYRjR Hf jddHNJ GdLRhdj GdHQHQj GdeQGcTj, CHh ehSi,J (B607 (3g` s
(3ChdgG (B:s
(3Chdg (B((3gPG HGH dG GdfGajg hdGHO ef ebOeI Hjf jOi GdHGH(B) s
(3BNQgG (B:s
(3jfJgi Edi BNQ HGH MQha GdJUOjb hGdEjLGH(B: (3fYe hMJi s
(3GdebOeI GdLRhdjI cGdMhGTi Ydi Led CHj GdbGSe GdRLGLis
(3LRA efgs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B104 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B27s
Keywords: (3GdfMhs